نظرية الوسائل في الشريعة الإسلامية : دراسة أصولية مقاصدية - بركانى، أم نائل (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2003)
This research deals with one of the important issues in Islamic jurisprudence in general, and the objectives of Shari'ah in particular. The research focuses on the means that lead to the objectives of the SharT'ah. It should be remembered that there are few studies devoted to the means of the objectives of Sharl' ah. Therefore, this study focuses on the means of the objectives of the Shari 'ah from an u~uti perspective. Most importantly, it aspires to construct a jurispredencial theory on the means of the objectives of Sharz'ah. A considerable attention is given to the relationship between ljtihad and this theory. This is meant to illustrate the defferent dimensions of the relationship, which includes the mujtahid, the tools of ljtihad and the sources, on which ljtihad is based. This is because it is essentially an historical and textual research based on the u~ulz literature. The research employs linguistic strategies of understanding the texts to reconstruct the defferent aspects of the theory of the means of the objectives of the Sharf'ah. The evidence of this research suggests that a clear demarcation should be made between the objectives of the Sharz'ah and the means to achieve these objectives. Certainly this distinction minimizes the defference between the jurists. Moreover, the jurists should be able to differentiate between divinely ordained means and the means, that were the result of human ljtihad. Finally, other internal distinctions should be considered when the rnujtahid deals with defferent parts of Islamic jurisprudence, such as rulings in worship matters, legal transactions and others. This research devots a considerable attention to the issue of "the end justifies the means" which is analyzed from a juristic view point. A number of typologies and distinctions are made for the understanding of this vital issue. However, the theory of the means of the objectives of Sharz'ah will assist the jurists to deal systematically with the issue.